Knowledge Representation for Computer-Aided Planning of Controlled Clinical Trials: the PATriCIa Project - Haag, U. (Methods of Information in Medicine, 1997)
The main thesis of the PATriCIa project is that a knowledge-based system can provide efficient and reliable support for biometricians as well as physicians involved in planning of controlled clinical trials, resulting in a higher quality of medical research. Structure and contents of study protocols are analyzed, and an object-oriented method for formally representing biometric knowledge is proposed. A study protocol can be generated from this formal representation. The programming language Prolog is used to realize the system based on a blackboard architecture. It is concluded that the knowledge representation method developed in the PATriCIa project is well suited for the purpose of generating study protocols for controlled clinical trials.
Keywords: Controlled Clinical Trials; Study Protocols; Knowledge-based System